Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency - DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (OXFORD UNIV PRESS, 2018)
Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of POI in adolescents. Both missense mutations identified in MRPS22 are rare, occurred in highly evolutionarily conserved residues, and are predicted to be deleterious to protein function. In contrast to prior reports of mutations in MRPS22 associated with severe mitochondrial disease, the POI phenotype is far less severe. Consistent with this genotype-phenotype correlation, mitochondrial defects in oxidative phosphorylation or rRNA levels were not detected in fibroblasts derived from the POI patients, suggesting a non-bioenergetic or tissue-specific mitochondrial defect. Furthermore, we demonstrate in a Drosophila model that mRpS22 deficiency specifically in somatic cells of the ovary had no effect on fertility, whereas flies with mRpS22 deficiency specifically in germ cells were infertile and agametic, demonstrating a cell autonomous requirement for mRpS22 in germ cell development. These findings collectively identify that MRPS22, a component of the small mitochondrial ribosome subunit, is critical for ovarian development and may therefore provide insight into the pathophysiology and treatment of ovarian dysfunction.
Keywords: TRANSFER-RNA SYNTHETASE; PRIMORDIAL GERM-CELLS; OF-FUNCTION MUTATIONS; SEQUENCING DATA; CHROMOSOMAL INSTABILITY; PERRAULT SYNDROME; GENETIC-VARIATION; TRANSGENIC RNAI; LACTIC-ACIDOSIS; HEARING-LOSS